MODE OF OCCURRENCE, TEXTURAL SETTINGS AND NITROGEN-ISOTOPIC COMPOSITIONS OF IN SITU DIAMONDS AND OTHER CARBON PHASES IN THE BENCUBBIN METEORITE - Mostefaoui S.; El Goresy A.; Hoppe P.; Gillet P.; Ott U. (My University, 2002)
Investigations on a polished thin section (PTS) by reflected-light microscopy, laser micro-Raman spectroscopy, and cathodoluminescence of the Bencubbin meteorite revealed the presence of diamond grains ranging in size from 200 nm to 1 μm in Fe-Ni metal, silicates, and at metal-silicate interfaces. Most of the diamonds are associated with poorly graphitized carbon (PGC). Nitrogen isotopic measurements with the new generation NanoSIMS 50 ion microprobe indicate the presence of two isotopically distinct types of nitrogen carriers: One carrier type consists of diamonds, their associated PGCs, and diamond-free PGCs (called group-B). It is N-poor and has isotopically close to normal N. The other carrier type consists only of diamond-free PGCs (called group-A), is N-rich and heavily enriched in 15N (δ15Nmax~1000%%). The petrographic and Raman characteristics of the diamonds are indicative of formation by shock. The difference in the N-isotopic compositions of diamonds and the associated group-B PGCs on the one hand, and the group-A diamond-free PGCs on the other, suggests that a 15N-rich component was probably incorporated into the Bencubbin parent body in an episode subsequent to the shock event that induced carbon-diamond phase transformation from the pristine PGCs with isotopically normal nitrogen. In the second episode, presumably in a milder shock event, significant amounts of N were delivered and redistributed among different phases. The isotopically heavy N signature is hence not pristine to the Bencubbin parent body, but was brought in by a second impactor.
Keywords: METEORITES; BENCUBBINITES; N-15/N-14; SHOCK-INDUCED DIAMONDS; NANOSIMS